2004
DOI: 10.1152/japplphysiol.00169.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and O2 uptake during maximal knee extensor exercise in untrained and trained human quadriceps muscle: effects of hyperoxia

Abstract: To elucidate the potential limitations on maximal human quadriceps O2 capacity, six subjects trained (T) one quadriceps on the single-legged knee extensor ergometer (1 h/day at 70% maximum workload for 5 days/wk), while their contralateral quadriceps remained untrained (UT). Following 5 wk of training, subjects underwent incremental knee extensor tests under normoxic (inspired O2 fraction = 21%) and hyperoxic (inspired O2 fraction = 60%) conditions with the T and UT quadriceps. Training increased quadriceps mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 35 publications
8
58
1
Order By: Relevance
“…Previous studies have found the 1-KE mass-specific O 2 uptake, measured by invasive methods, to range from 350 to 602 ml·kg -1 ·min -1 (Andersen & Saltin, 1985i;Rowell et al, 1986;Richardson et al, 1993a;Radegran et al, 1999a;Richardson et al, 1999a;Mourtzakis et al, 2004). The mass specific O 2 uptake found in the present study of 386 and 570 ml·kg -1 ·min -1 for controls and ET, closely agree with this range.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have found the 1-KE mass-specific O 2 uptake, measured by invasive methods, to range from 350 to 602 ml·kg -1 ·min -1 (Andersen & Saltin, 1985i;Rowell et al, 1986;Richardson et al, 1993a;Radegran et al, 1999a;Richardson et al, 1999a;Mourtzakis et al, 2004). The mass specific O 2 uptake found in the present study of 386 and 570 ml·kg -1 ·min -1 for controls and ET, closely agree with this range.…”
Section: Discussionsupporting
confidence: 89%
“…In the ''restricted blood flow'' condition all training was performed with an occlusion cuff, whereas the contralateral limb training was performed without restriction. It has been recently demonstrated that changes in vascular capacity are limited to the trained region following resistance training (Alomari and Welsch 2007) and there are no cardiovascular effects on the contra-lateral limb (Mourtzakis et al 2004;Saltin et al 1976). All pretraining tests were performed 3-5 days prior (baseline) to the commencement of the resistance training programme and post-training measurements performed 3-5 days after the final training session.…”
Section: Overview Of Experimental Proceduresmentioning
confidence: 99%
“…The quadriceps training induced increases in peak work rate of 24% (Mourtzakis et al 2004), and the relative load on the trained versus the untrained leg was therefore also different during the 3 h two-legged exercise. The subjects performed two-legged knee extensor exercise for 3 h at 87±5 W, and as the two legs performed similar amount of work (Pilegaard et al 2003), i.e.…”
Section: Choice Of Exercise Intensitymentioning
confidence: 99%